Comparison of the Wise and Philosophical Ideas in Ferdowsi’s Shahnameh and Nasser Khusraw’s Book of Poems - Zanalimahmodabadi, Maliheh; Amirahmadi, Aboalqasm; Eshghisardehi, Ali (Journal of History Culture and Art Research, 2017)
History of Iran has deep links with Shahnameh and Persian literature. In fact, it is not possible to talk about Iran as a rich culture and disregard Persian literature and brilliant works of Persian literature. According to most scholars in the field of literature and culture, Iranians have been people of wisdom, thought, and philosophy. Ferdowsi and Nasser Khusraw hold a special place in this regard because we are faced with ethical, philosophical, and religious ideas in the works of both poets. Different effects of the Iranian Wisdom are presented in their poems; the effects include ethics, philosophy, logic, medicine, music, determinism and free will, fate, arithmetic and geometry, astronomy etc. Ferdowsi’s Shahnameh and Nasser Khusraw’s Book of Poems are sublime manifestation of ideological and philosophical ideas of Iranians. Apart from the similarities and differences, Ferdowsi and Nasser Khusraw’s poems represent praise of wisdom, God, and human freedom as basic elements in the ontology of Persian culture. Hence, in addition to understanding and explanation of Ferdowsi, Nasser Khusraw’s day and age, and the importance of these two poets in Iran's development of wisdom and philosophical thought, this research tries to describe their similarities and differences in ideological and philosophical subjects.